Perspectives for the Implementation of Euro Currency in Poland - Sporek, Tadeusz (Perspektywy wprowadzenia przez Polskę wspólnej waluty euro, 2009)
The cost and benefit analysis of introducing euro in Poland does not lead to a conclusion that the rich benefit and the poor lose. Some adverse effects for the poorer part of the population albeit of a limited scale may appear only in the process of fulfilling the Maastricht criteria and in the moment of physical replacement of zloty by euro.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 81, s. 131-142
Keywords: euro; euro zone; the European Central Bank; inflation; risk